Mechanisms of white matter change induced by meditation training - Posner, Michael I.; Tang, Yi-Yuan; Lynch, Gary (Frontiers in Psychology, 2014)
Training can induce changes in specific brain networks and changes in brain state. In both cases it has been found that the efficiency of white matter as measured by Diffusion Tensor Imaging is increased, often after only a few hours of training. In this paper we consider a plausible molecular mechanism for how state change produced by meditation might lead to white matter change. According to this hypothesis frontal theta induced by meditation produces a molecular cascade that increases myelin and improves connectivity.